A chaotic potential of charged dislocations in group III-nitride heterojunctions during localization of a two-dimensional electron gas - Filimonov Alexey; Bondarenko Vyacheslav (St. Petersburg Polytechnical University Journal: Physics and Mathematics, 2024)
This work studies a chaotic potential (CP) in the heterojunctions of III-nitrides, the CP caused by the electrostatic field of charged dislocations, under localization conditions of a two-dimensional electron gas in the near-contact region. Within the framework of the statistical analysis of a Poisson ensemble of linear defects, the amplitude and scale of the CP in the contact plane have been determined. The CP parameter dependence on the density of surface states and the concentration of dislocations at the mobility threshold of the two-dimensional electron gas was shown. The CP amplitude was established to exceed 100 meV in a wide range of changes in the system parameters, in the presence of electronic charge localization effects in the heterojunctions.